ANALISIS PENDAPATAN USAHA BERBAGAI UKM MAKANAN CAMILAN BERBASIS UBI KAYU DI KECAMATAN MARTAPURA KABUPATEN OGAN KOMERING ULU TIMUR - Henny Rosmawati, Lega Arda Lewa, Septianita, Endang Lastinawati (JASEP, 2024)
This research aims to analyze the business income of various cassava-based snack food SMEs in Martapura District, East Ogan Komering Ulu Regency. This research was carried out in Martapura District, East Ogan Komering Ulu Regency from April to June 2019. The method used in this research was a survey method. Sampling in this research used the saturated sample method. The research results show that the income of Kelanting SMEs in Martapura District, East Ogan Komering Ulu Regency is IDR 6,530,500.00 per month. The income of SMEs from sweet potato chips in Martapura District, East Ogan Komering Ulu Regency is IDR 10,521,542.86 per month, and the income of SMEs from sweet potato chips and kelanting in Martapura District, East Ogan Komering Ulu Regency is IDR 9,561,187.50 per month.